The effects of microRNA-126 reduced inflammation and apoptosis of diabetic nephropathy through PI3K/AKT signalling pathway by VEGF. (3rd September 2022) - Lou, Zhe; Li, Qiaobei; Wang, Chunyan; Li, Yinyan
Abstract: Gene expression microarray and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to measure the expression of miR-126. In model of diabetic nephropathy, we demonstrated that miR-126 expression was down-regulated, compared with control group. Down-expression of miR-126 promoted cell apoptosis and increased inflammation (as indicated by the levels of IL-1β, IL-6, IL-18 and TNF-α) of diabetic nephropathy in vitro . miR-126 over-expression led to significant inhibition of cell apoptosis and suppressed inflammation (IL-1β, IL-6, IL-18 and TNF-α). However, the down-expression of miR-126 suppressed the protein expression of VEGF, PI3K and p-AKT in diabetic nephropathy in vitro . On the contrary, over-expression of miR-126 induced the protein expression of VEGF, PI3K and p-AKT in diabetic nephropathy in vitro . The inhibition of VEGF increased the effect of miR-126 down-expression on apoptosis and inflammation in diabetic nephropathy in vitro . We investigated the specific function of miR-126 in patients with diabetic nephropathy and its possible mechanism.